2018
DOI: 10.15537/smj.2018.5.22058
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based synthesis for prevention of noninvasive ventilation related facial pressure ulcers

Abstract: The last 2 decades have seen a growing trend towards the use of noninvasive ventilation (NIV) therapy in the management of many conditions that cause acute respiratory failure. However, there is a serious side effect that results in using these devices; the development of facial skin pressure damage, specifically pressure ulcers. This skin damage has a considerable effect on patients’ quality of life, treatment adherence and patients’ comfort in addition to the therapy challenges of wound care. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 46 publications
1
32
0
2
Order By: Relevance
“…Tsu-boi et al [33] demonstrated that nasal intermittent positive pressure ventilation delivered with custom-fabricated nasal mask was more effective than nasal intermittent positive pressure ventilation applied with a commercially available mask due to the smaller dead space and the less amount of leaks. Custom-made interfaces were also associated with less skin breakdown [54,[60][61][62] as compared to commercial "ready-to-use" masks [50]. Custom masks have been employed for a long time, but now their use is limited almost exclusively to the paediatric setting [49].…”
Section: Mask Classification and Materialsmentioning
confidence: 99%
“…Tsu-boi et al [33] demonstrated that nasal intermittent positive pressure ventilation delivered with custom-fabricated nasal mask was more effective than nasal intermittent positive pressure ventilation applied with a commercially available mask due to the smaller dead space and the less amount of leaks. Custom-made interfaces were also associated with less skin breakdown [54,[60][61][62] as compared to commercial "ready-to-use" masks [50]. Custom masks have been employed for a long time, but now their use is limited almost exclusively to the paediatric setting [49].…”
Section: Mask Classification and Materialsmentioning
confidence: 99%
“…Interfaces influence compliance, comfort, synchrony, and ventilators' performance ( 6 , 7 ). An ideal interface is lightweight, is stable, is non-traumatic, has minimal dead space, is durable, has low resistance to airflow, is available in several sizes, is easy to clean and disinfect, is connectable with any ventilator, is easy to take off in order to avoid aspiration if the ventilator crashes or the patient vomits, and is affordable ( 8 , 9 ).…”
Section: Interfacesmentioning
confidence: 99%
“…Skin lesions are frequent adverse events associated with NIV masks ( 9 ). Since impermeable silicone polymers are the most frequently used contact materials, increased humidity can provoke skin maceration and, consequently, increased risk of cutaneous lesions ( 8 ).…”
Section: Interfacesmentioning
confidence: 99%
See 2 more Smart Citations